Paradigm based Hindi morphological analyzer - Kumar, Vishal (My University, 2013)
Morphology is the field of linguistics that studies the internal structure of the words. it deals with the identification, analysis and description of the structure of a given language's morphemes and other linguistic units, such as root words, affixes, part of speech, intonation/stress or implies context.
Masters of Engineering (ME.CSE)
Keywords: Morphology; hindi; morphological analyzer; paradigm